(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The way business owners interact with their customers has changed as a result of global technological advancement. Businesses currently use various marketing strategies, such as social media, to get customers’ attention, interest, desire, and action. (Hassan et al. 2018). Tinybop Inc. is a business in Bahay Toro, Quezon City that sells baby garments. They are using social media as their marketing strategy in order to gain sales, and most of their inquiries and transactions are conducted online. However, there are instances that their existing social media marketing strategies are not enough to attract new customers and convince their existing customers to repurchase. The findings of the study revealed that there is a very positive correlation between the assessment of social media marketing strategies and customer decision-making. The findings also revealed the assessment of social media marketing strategies of Tinybop Inc. in terms of representation, engagement, and listening-in and assessment of customer decision-making in terms of awareness, research, consideration, conversion, and repurchase. This study recommends that Tinybop Inc. should provide a budget for their social media marketing. Hire experienced social media managers and get more influencers to promote and boost their products online. Also, Tinybop Inc. must be updated to the latest trends to maintain customer retention.